Development and optimization of polymeric nanoparticles of antitubercular drugs using central composite factorial design - Chawla R.; Jaiswal S.; Mishra B. (My University, 2025)
Objective: The objective of the present study was to develop sustained release biodegradable polymeric nanoparticles (PNs) of two anti-tubercular drugs (ATDs), rifampicin (RIF) and isoniazid (INH) using circumscribed central composite factorial design (CCD) and evaluate in vivo uptake potential using rhodamine labeled PNs (RPNs). Methods: CCD was employed to study the influence of independent formulation factors, drug:polymer ratio (D:P) and surfactant concentration (SC), on dependent physicochemical characteristics, particle size (PS), polydispersity index (PI) and percentage entrapment efficiency (%EE) of the drugs. Optimized PNs prepared using response surface methodology (RSM) were evaluated for in vitro kinetics at endosomal macrophage pH 5.2 and physiological pH 7.4 and in vivo targeting potential in peritoneal macrophages (PMs) by fluorescence microscopy (FM) and confocal laser scanning microscopy (CLSM). Results: Optimized PNs exhibited spherical and porous surface with a mean PS of 202 nm, PI of 0.178, zeta potential of -25.49 mV and %EE of 76.12% and 54.25% for RIF and INH, respectively. Conclusions: Highly hydrophilic INH could be encapsulated with lypophilic RIF with efficiency. In vivo uptake studies of RPNs in PMs suggested endocytosis of RPNs without any surface adsorption phenomenon. Hence, further studies need to be performed for establishing the pharmacokinetic potential of PNs. © 2014 Informa UK, Ltd.